SYSTEMIZATION OF NURSING DISCHARGE - AN ANALYSIS BASED ON ROY - Emanuelle Caires Dias Araújo Nunes; Nilton Alves de Menezes Filho (Universidade Federal do Paraná, 2016)
Abstract The objective was to analyze the systemization process of hospital discharge based on Roy's Adaptation Model. A qualitative study was developed at a public hospital in the interior of Bahia, involving 12 subjects, including nurses and people/families, delimited by the saturation of the data. The data were collected between June and August 2015, involving semistructured interviews and non-participant observation of the nursing team, with data treated through thematic analysis. The results were organized along five axes: assessment of the person's behavior; assessment of the person's stimuli; establishment of objectives for discharge; preparatory intervention for discharge; and assessment of the discharge process. The axes were presented from three angles: what was said, what was done and what was expected. In conclusion, discharge planning and intervention remains incipient, suggesting to the professionals the need to systemize the "Nursing Discharge Plan" based on Roy.